2019
DOI: 10.1152/ajprenal.00234.2018
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of enhancer of zeste homolog 2 alleviates renal injury associated with hyperuricemia

Abstract: Hyperuricemia has been identified as an independent risk factor for chronic kidney disease (CKD) and is associated with the progression of kidney diseases. It remains unknown whether enhancer of zeste homolog 2 (EZH2), a histone H3 lysine 27 methyltransferase, can regulate metabolism of serum uric acid and progression of renal injury induced by hyperuricemia. In this study, we demonstrated that blockade of EZH2 with 3-DZNeP, a selective EZH2 inhibitor, or silencing of EZH2 with siRNA inhibited uric acid-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 73 publications
2
21
0
Order By: Relevance
“…5 Several forms of epigenetic modifications, including DNA methylation, microRNA and histone modifications, have been identified. [7][8][9] As demonstrated in previous study, EZH2 inhibition alleviated I/R-induced AKI by modulating P38 signaling, indicating that EZH2 might be a novel therapeutic target for I/R-mediated AKI. 6 Enhancer of zeste homolog 2 (EZH2), a type of histone methyltransferases, is well known as the main catalytic part of polycomb repressive complex 2 (PRC2) and plays a vital role in triggering trimethylation of histone H3 at lysine27, which has been reported to be involved in the progression of a variety of kidney disease models, including renal I/R injury.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…5 Several forms of epigenetic modifications, including DNA methylation, microRNA and histone modifications, have been identified. [7][8][9] As demonstrated in previous study, EZH2 inhibition alleviated I/R-induced AKI by modulating P38 signaling, indicating that EZH2 might be a novel therapeutic target for I/R-mediated AKI. 6 Enhancer of zeste homolog 2 (EZH2), a type of histone methyltransferases, is well known as the main catalytic part of polycomb repressive complex 2 (PRC2) and plays a vital role in triggering trimethylation of histone H3 at lysine27, which has been reported to be involved in the progression of a variety of kidney disease models, including renal I/R injury.…”
Section: Introductionsupporting
confidence: 58%
“…6 Enhancer of zeste homolog 2 (EZH2), a type of histone methyltransferases, is well known as the main catalytic part of polycomb repressive complex 2 (PRC2) and plays a vital role in triggering trimethylation of histone H3 at lysine27, which has been reported to be involved in the progression of a variety of kidney disease models, including renal I/R injury. [7][8][9] As demonstrated in previous study, EZH2 inhibition alleviated I/R-induced AKI by modulating P38 signaling, indicating that EZH2 might be a novel therapeutic target for I/R-mediated AKI. 10 Simultaneously, numerous evidences demonstrated that EZH2 was linked to a variety of cellular responses, such as apoptosis and inflammation.…”
Section: Introductionsupporting
confidence: 58%
“…Under the stimulation of cytokines and growth factors, fibroblasts undergo activation and proliferation, achieve myofibroblast phenotype, and synthesize ECMs, including structural scaffolds, fibronectin, and various types of collagens [ 82 ]. UA promotes the renal fibroblast–myofibroblast transition mainly through the activation of the TGF- β /Smad3, epidermal growth factor receptor (EGFR), and ERK1/2 pathways [ 83 , 84 ]. However, after treatment with 3-deazaneplanocin A, a selective inhibitor of the enhancer of zeste homolog 2, the above-activated pathways were inhibited, and the proliferation of renal fibroblasts was suppressed, alleviating renal interstitial fibrosis [ 83 ].…”
Section: Mechanisms Of Hyperuricemia-induced Renal Injurymentioning
confidence: 99%
“…UA promotes the renal fibroblast–myofibroblast transition mainly through the activation of the TGF- β /Smad3, epidermal growth factor receptor (EGFR), and ERK1/2 pathways [ 83 , 84 ]. However, after treatment with 3-deazaneplanocin A, a selective inhibitor of the enhancer of zeste homolog 2, the above-activated pathways were inhibited, and the proliferation of renal fibroblasts was suppressed, alleviating renal interstitial fibrosis [ 83 ].…”
Section: Mechanisms Of Hyperuricemia-induced Renal Injurymentioning
confidence: 99%
“…Increasing evidence shows that EZH2 is associated with a variety of kidney diseases and pathology. In addition to the abnormal expression and activation of EZH2 in renal tumors, its expression levels and activity were also increased in acute kidney injury (AKI; Zhou et al, 2018b ), renal fibrosis ( Zhou et al, 2016 ), diabetic nephropathy (DN; Jia et al, 2019b ), lupus nephritis (LN; Rohraff et al, 2019 ), hyperuricemic nephropathy ( Shi et al, 2019 ), and transplanted and aging kidneys ( Li et al, 2016 ; Han and Sun, 2020 ). Moreover, pharmacological or genetic inhibition of EZH2 can interfere with pathologic fibrosis in these animal models of kidney disease.…”
Section: Introductionmentioning
confidence: 99%